Selection of 2,6-Di-tert-butyl-4-methylphenol and High Purity Alkylated Phenyl-a-naphthylamine and Their Synergy Antioxidation Mechanism in Insulation Oil - Liao, Ruijin; Hao, Jian; Yang, Lijun; Liang, Shuaiwei; Zhu, Mengzhao (Asian Journal of Chemistry, 2011)
In order to improve the oxidation stability of a new insulation oil derived from mineral oil and natural ester, 2,6-di-tert-butyl-4-methylphenol (DBPC) and high-purity alkylation-a-naphthylamine (HPAN) have been selected as the composite antioxidant in the oil by using pressure differential scanning calorimetry. Pressure differential scanning calorimetry results show that the composite antioxidant can enhance the oxidation stability of the new insulation oil significantly and make its oxidation stability more superior to mineral oil. Molecular simulation and fourier transform infrared spectroscopy results indicate that it is the synergistic antioxidant effect of DBPC and HPAN improving the oxidation stability of the new insulation oil. At last, a preliminary analysis of the synergistic mechanism of the composite antioxidant was proposed.